2012
DOI: 10.1103/physreve.85.031906
|View full text |Cite
|
Sign up to set email alerts
|

Soliton concepts and protein structure

Abstract: Structural classification shows that the number of different protein folds is surprisingly small. It also appears that proteins are built in a modular fashion, from a relatively small number of components. Here we propose to identify the modular building blocks of proteins with the dark soliton solution of a generalized discrete nonlinear Schrödinger equation. For this we show that practically all protein loops can be obtained simply by scaling the size and by joining together a number of copies of the soliton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(129 citation statements)
references
References 19 publications
3
118
0
7
Order By: Relevance
“…In [21] we have found that most crystallographic protein structures in PDB can be described in a modular fashion and with experimental B-factor precision, by combining together no more than 200 explicit soliton profiles. We propose that by learning how to compute the parameter values directly from the sequence, the geometric shape of most folded proteins can be constructed simply by solving the Master equation (28).…”
Section: G: Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In [21] we have found that most crystallographic protein structures in PDB can be described in a modular fashion and with experimental B-factor precision, by combining together no more than 200 explicit soliton profiles. We propose that by learning how to compute the parameter values directly from the sequence, the geometric shape of most folded proteins can be constructed simply by solving the Master equation (28).…”
Section: G: Parametersmentioning
confidence: 99%
“…This makes a strong case that the solitons of the DNLS equation are the modular building blocks of folded proteins [21].…”
Section: D: Soliton Ansatzmentioning
confidence: 99%
See 1 more Smart Citation
“…But we have found [32][33][34] that an excellent approximative solution can be obtained by discretizing the topological soliton (43).…”
Section: Discretized Solitonsmentioning
confidence: 99%
“…Indeed, it has been shown that over 92% of all Cα-traces of PDB proteins can be described by 200 different parametrizations of the discretized NLS kink (69), with better than 0.5Å root-mean-square-distance (RMSD) precision [34]. Accordingly, we set up to describe the modular building blocks of proteins in terms of various parametrizations of the DNLS soliton profile, that is described by the equations (68), (66), (58) and (59).…”
Section: Solitons and Proteinsmentioning
confidence: 99%